Nanoconfined lithium aluminium hydride (LiAlH4) and hydrogen reversibility - Wang, L.; Rawal, A.; Quadir, Md Zakaria; Aguey-Zinsou, K. (Elsevier Ltd, 2017)
Lithium aluminium hydride (LiAlH4) is a promising hydrogen storage material with a storage capacity of 10.6 mass % H2. However, its practical use is hampered by the lack of direct rehydrogenation routes. In this study, we report on the confinement of LiAlH4into the nanoporosity of a high surface area graphite resulting in a remarkable improvement of its hydrogen storage properties. Nanoconfined LiAlH4started hydrogen desorption near 135 °C and after full dehydrogenation at 300 °C limited rehydrogenation was observed at the same temperature and 7 MPa of hydrogen pressure. Rehydrogenation took place through the formation of Li3AlH6with some limited rehydrogenation back to LiAlH4indicating the existence of different (de)hydrogenation paths upon nanoconfinement as compared to the known dehydrogenation path of bulk LiAlH4.